Advantages of Export Promotion Policy in Rural Farming and Factors Conditioning It - Asgarov, Ramil (Acta Universitatis Danubius. Œconomica, 2024)
As is known, agriculture is considered one of the crucially important sectors of the economy. Therefore, ensuring food security is directly dependent on the continuous development of agriculture. It should be noted that in developing countries, especially for oil-exporting countries, the role of agriculture is significantly elevated in the development of the non-oil sector and the implementation of alternative export policies. Given all these considerations, the implementation of export promotion policies in agriculture plays a particularly significant role. Export promotion policies in agriculture are understood to involve measures aimed at stimulating producers domestically and providing practical assistance to agricultural producers for the increase of export sales. In general, the promotion of exports is directly dependent on the implementation of trade policies domestically and the enhancement of business attractiveness. The experience of developed countries indicates that measures aimed at promoting exports, such as providing export credits to agricultural producers and offering necessary guarantees to them, directly contribute to increasing the volume of purchases domestically, thus reflecting measures aimed at increasing the level of economic activity.